2010
DOI: 10.14295/bds.2003.v6i3.602
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do ângulo nasolabial, em radiografias cefalométricas laterais, dividido em ângulo superior e inferior, por uma linha paralela ao plano de Frankfort, em indivíduos portadores de má-oclusão classe II e classe III de angle

Abstract: Este estudo constou da análise do ângulo nasolabial e sua divisão em superior e inferior, por uma linha paralela ao Plano de Frankfort passando pelo ponto subnasal. Foram utilizadas 120 radiografias cefalométricas norma lateral, em pacientes portadores de má-oclusão Classe II e Classe III de Angle, 60 de cada grupo, 30 do sexo feminino e 30 do sexo masculino, na faixa etária de 13 a 43 anos, com média de idade de 241,03+77,78 meses. Os resultados obtidos foram para o ângulo nasolabial média para toda amostra d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…The nasolabial angle (Prn-Sn-UL) had significant changes (p≤0.05) between the two time points as a result of nasal growth and upper lip retraction, which takes place during the normal development of individuals, when the nasolabial fold may also become longer. 7 The results are in agreement with those reported by Salgado et al, 26 who found significant variations in nasolabial angles of individuals with Angle Class II and Class III malocclusion, and greater values in Class II cases. However, the results differ from those reported by Brant et al, 3 who found no significant differences in the nasolabial angle of individuals that underwent orthodontic treatment with or without extractions.…”
Section: Discussionsupporting
confidence: 91%
“…The nasolabial angle (Prn-Sn-UL) had significant changes (p≤0.05) between the two time points as a result of nasal growth and upper lip retraction, which takes place during the normal development of individuals, when the nasolabial fold may also become longer. 7 The results are in agreement with those reported by Salgado et al, 26 who found significant variations in nasolabial angles of individuals with Angle Class II and Class III malocclusion, and greater values in Class II cases. However, the results differ from those reported by Brant et al, 3 who found no significant differences in the nasolabial angle of individuals that underwent orthodontic treatment with or without extractions.…”
Section: Discussionsupporting
confidence: 91%
“…Médias (M) DP Médias (F) DP t P 21 , ao avaliarem 60 pacientes brasileiros com Classe III, também encontraram a média do ângulo nasolabial dentro dos padrões de normalidade (103,48°). Já Robison et al 22 investigaram a relação do padrão esquelético facial com a forma do nariz e relataram que o grupo Classe III esquelética apresentou a média do ângulo nasolabial um pouco mais elevado, mas ainda dentro da faixa normal (109,61°).…”
Section: Variáveisunclassified